Bat humoral immunity and its role in viral pathogenesis, transmission, and zoonosis - Roffler, Anne A.; Maurer, Daniel P.; Lunn, Tamika J.; Sironen, Tarja; Forbes, Kristian M.; Schmidt, Aaron G. (Frontiers in Immunology, 2024)
Bats harbor viruses that can cause severe disease and death in humans including filoviruses (e.g., ebola virus), henipaviruses (e.g., Hendra virus) and coronaviruses (e.g., SARS-CoV). Bats often tolerate these viruses without noticeable adverse immunological effects or succumbing to disease. Previous studies have largely focused on the role of the bat innate immune response to control viral pathogenesis, but little is known about bat adaptive immunity. A key component of adaptive immunity is the humoral response, comprised of antibodies that can specifically recognize viral antigens with high affinity. The antibody genes within the 1,400 known bat species are highly diverse, and these genetic differences help shape fundamental aspects of the antibody repertoire, including starting diversity and viral antigen recognition. Whether antibodies in bats protect, mediate viral clearance, and prevent transmission within bat populations in poorly defined. Furthermore, it is unclear how neutralizing activity and Fc-mediated effector functions contribute to bat immunity. Although bats have canonical Fc genes (e.g., mu, gamma, alpha, epsilon), the copy number and sequences of their Fc genes differ from humans and mice. The function of bat antibodies targeting viral antigens have been speculated based on sequencing data and polyclonal sera, but functional and biochemical data of monoclonal antibodies are lacking. In this review, we summarize current knowledge of bat humoral immunity, variation between species, potential role(s) in protection against and transmission of viruses, and address how these antibodies may contribute to viral population dynamics within bats. A deeper understanding of bat adaptive immunity will provide insight into immune control of transmission and replication for emerging viruses with the potential for zoonotic spillover.